Imaginary Space and its Representation by the Narrator (Based on the Example of the Novel “the Diamond as Big as the Ritz” of S. Fitzgerald) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
"Imaginary space" in literature includes the area of the mind where characters' thoughts, emotions, and inner conflicts reside. It's a concept that allows authors to explore the psychological depths of their characters and convey complex themes and ideas. Narrators often play a crucial role in representing these imaginary spaces by providing insights into characters' inner workings through  introspective narration, inner monologues, and clear descriptions.